Institution of a centralized employee database for inland freight truckers - Ramos, Maridelle Medina (Animo Repository, 2012)
This thesis explored the legal and economic ramifications in implementing a proposed centralized employees’ database for Inland Freight Trucking Companies in North Harbor and South Harbor. The database is primarily proposed to mitigate the number of instances of hijacking, pilferage and other trucking-related crimes, as well as the monitoring of the employees and employers in the industry. It is presented that in implementing the said database, right to privacy of the employees will be violated. It is also raised that the database supports the right to information of the employers to the employees’ actual background, which is essential in hiring process of the trucking companies. It is further presented that as part of the duty of extraordinary diligence required by law for common carriers such as the trucking companies, it is also the employers’ duty to hire competent and trustworthy employees in furtherance of assuring safe transportation of goods from one place to another. Further, it is submitted that there are economic implications on the part of the end users of the said database, such as the costs and effect on the business. To test this, there were 50 survey employer participants and 50 survey employee participants, which are all members of the Inland Freight Trucking Industry. Further, eight expert interviewees were conversed with to clarify and to answer questions relating to the implementation of the database. The researcher found that the implementation of the database per se does not violate the right to privacy of the employees, except when the entity viii responsible for the management of the database is a government agency, in which case, it could be subjected to violation of privacy, depending on the circumstances. Results also show that the database is really in support of the right to information and the duty of the employers to exercise extraordinary due diligence in performing their functions. Employers are in support of its implementation and both the employers and employees agree that there is a necessity in the immediate implementation of the proposed database. However, when it comes to the costs in enrolling themselves in the database, the employees were very hesitant in paying the services of the database. On the other hand, the employers would still want to pursue the implementation of the database but a few have concerns with the costs. This investigation presents an initiative to corporate governance and step towards progress that would help develop or push forward the industry as a whole. The researcher recommends that further exploration is need to determine the feasibility of this study, specifically on the software design and physical infrastructure of the database.